Women and the Emancipative Projects of Bulgarian Modernity - Vacheva, Albena (Poznańskie Studia Slawistyczne, 2016)
The main focus of the current study is the role of periodicals in the emancipation of the woman in a modernizing Bulgarian society. From a social and political perspective, female virtues, rights and duties become an object of varied debates in Bulgaria at the end of the 19th – beginning of the 20th centuries. Women’s newspapers and magazines participate actively in these debates whilst familiarizing their female readers with the ideas and struggles of women in Western Europe, presenting diverse philosophical concepts, and discussing established cultural models. In these periodicals there appear materials which endeavour to cultivate models of emancipative behaviour; these publications include translations and authentic literature with a „feminine” axis. Female identity in this period gets formed within respective periodicals and the circles clinging to them, and it comes to represent a complex entity of, on the one hand, radical concepts stressing equality and female rights, and, on the other, conservative perceptions of the place of the woman in the modern household environment.